Jewish-Muslim relations and migration from Yemen to Palestine in the late nineteenth and twentieth centuries - Ariel, Ari (Brill, 2013)
In Jewish-Muslim Relations and Migration from Yemen to Palestine in the Late Nineteenth and Twentieth Centuries Ari Ariel provides an account of Jewish emigration out of Yemen from 1880 to 1950.